A food-based approach introducing orange-fleshed sweet potatoes increased vitamin A intake and serum retinol concentrations in young children in Mozambique - Low, Jan W.; Arimond, Mary; Osman, Nadia; Cunguara, Benedito; Zano, Filipe; Tschirley, David (International Food Policy Research Institute, 2007)
Vitamin A deficiency is widespread and has severe consequences for young children in the developing world. Food-based approaches may be an appropriate and sustainable complement to supplementation programs. Orange-fleshed sweet potato (OFSP) is rich in ß-carotene and is well accepted by young children. In an extremely resource poor area in Mozambique, the effectiveness of introduction of OFSP was assessed in an integrated agriculture and nutrition intervention, which aimed to increase vitamin A intake and serum retinol concentrations in young children... The study showed that integrated promotion of OFSP can complement other approaches and contribute to increases in vitamin A intake and serum retinol concentrations in young children in rural Mozambique and similar areas in Sub-Saharan Africa.